Structural evaluation of the effects of chronic ethanol ingestion on the testis of Calomys callosus - Martinez, M.; Macera, S.; Assis, G. F. de [UNESP]; Pinheiro, P. F. F. [UNESP]; Almeida, C. C. D. [UNESP]; Tirapelli, L. F.; Martins, O. A. [UNESP]; Mello Júnior, Wílson de [UNESP]; Padovani, C. R. [UNESP]; Martinez, Francisco Eduardo [UNESP] (Churchill Livingstone, 2009)
Chronic exposure to ethanol may results in pathophysiologic changes in cellular function. The present work was designed to investigate the morphology of testis submitted to experimental ethanol ingestion. Experimental animals were divided into two groups. The control group (n = 23) received a solid diet and tap water and the alcoholic group (n = 23) received the same solid diet and ethanol P.A. diluted 20% in water (v/v). After 120 days of treatment, all animals were anesthetized, weighed and sacrificed. Testosterone and luteinizing hormone levels in serum were lower in the alcoholic group than in the control group. Histological and ultrastructural alterations were observed in the testicular alcoholic germinative cells like enormous spaces, lipid droplets accumulation, digestive vacuoles, irregular diameter of the seminiferous tubules and interstitial dilated blood vessels. It was concluded that 20% ethanol provokes lesions on the testis germinative epithelium probably inducing gonadal dysfunction. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Testis; Structure; Ethanol; Calomys callosus